PROMOSI POTENSI WISATA MELALUI PENDAMPINGAN PRODUKSI PHOTO STORY BAGI SISWA SMK DI KABUPATEN MAGETAN - Johan Ies Wahyudi; Purwastya Pratmajaya; Setyo Bagus Waskito (Abdi Seni, 2019)
Magetan is a district located in the province of East Java. Geographical location of Magetan Regency located on the slopes of Mount Lawu in the east, making Magetan rich in natural tourism potential of the mountains. From year to year, the tourism potential of Magetan regency is increasing, with the construction of artificial tourism object with the natural concept of the mountains that is cool and beautiful. To be interesting, if the youth of Magetan district, especially high school / vocational school students have the potential to make promotional materials about tourism potential owned by his own residence.By using participatory methods, the workshop participants are trained to be skilled in creating promotional materials in the form of photo story. The participatory method is considered to be the most appropriate choice because it puts a balanced position between teacher / facilitator and student / trainee.The purpose of this Community Service Program is to create collective awareness from various parties especially young people to build community capacity, in order to build Magetan district especially in order to increase tourism potential of Magetan regency. It is also hoped that the resulting photo story can be a reflection of the stakeholders in order to increase the tourism potential of Magetan Regency.Keywords: tourism potential, Magetan, student, photo story.